Discursive genres in the literacy of children in multigroup classes in rural schools - Dilmar Rodrigues da Silva Junior (Revista Brasileira de Educação do Campo)
This article has the following object of study: Discursive genres in the literacy of children in multigrade classes in rural schools. It needs to answer the following problem question: How can we enable the literacy of children in multi-grade classes to privilege the use of discursive genres? Considering the proposed question, we set ourselves the following objective: to understand the work with discursive genres in the literacy process of children in multigrade classes in rural schools. The concept of literacy that underpins the research is based on cultural-historical theory, which links literacy and literacy. It is a study guided by the principles of the autobiographical method, consolidated through narrative research, according to Dominicé's (1988) propositions. The narratives were produced through biographical memorials. Based on the collaborators' narratives, the study found that literacy requires the organization of time, space and the availability of reading and writing materials.